Raoultella planticola bacteremia-induced fatal septic shock following burn injury - Yumoto, Tetsuya (Ann Clin Microbiol Antimicrob, 2018)
BACKGROUND: Raoultella planticola, a Gram-negative, aerobic bacillus commonly isolated from soil and water, rarely causes invasive infections in humans. Septic shock from R. planticola after burn injury has not been previously reported. CASE PRESENTATION: A 79-year-old male was admitted to the emergency intensive care unit after extensive flame burn injury. He accidently caught fire while burning trash and plunged into a nearby tank filled with contaminated rainwater to extinguish the fire. The patient developed septic shock on day 10. The blood culture detected R. planticola, which was identified using the VITEK-2 biochemical identification system. Although appropriate antibiotic treatment was continued, the patient died on day 12. CONCLUSIONS: Clinicians should be aware of fatal infections in patients with burn injury complicated by exposure to contaminated water.